Analisis Tanggung Gugat Penyedia Jasa Tindik (Piercing) di Indonesia dalam Kerangka Hukum yang Berlaku di Indonesia - Felicia Angela Prasetyo; Mezaluna Erga Azzahra; Shabrina Ramadhani S.; Armilda Febriana (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Piercing is a popular form of body modification in Indonesia that has led to the emergence of many piercing services. Every consumer has the right to security and safety in using services as emphasized in Law Number 8 Year 1999 on Consumer Protection. Every piercing service provider is obliged to fulfill consumer rights and obligations as a good faith service provider. However, until now the Indonesian legal system has not specifically regulated the practice of piercing and the liability of piercing service providers if consumers suffer losses due to procedural errors or malpractice. This causes the position of consumers to be very weak and need to get legal protection. This study uses a normative-juridical approach to analyze the urgency of legal regulation and liability of piercing service providers in Indonesia and to compare the regulation of piercing practices with the United States. Legal provisions related to the practice of piercing in the United States have been regulated in detail through licensing, sterilization training, and strict health supervision so as to provide legal protection for consumers. The results showed that legal arrangements related to the practice of piercing in Indonesia are still general and do not specifically address the technical standardization of piercing procedures, resulting in the absence of adequate consumer protection. Consequently, if losses occur, service providers are held liable. Based on this research, it is deemed necessary to formulate specific legal regulations regarding piercing practices in Indonesia in order to ensure safety, health, and legal certainty.